The Role of Indonesian Constitutional Court In Protecting Energy Security - Armia, Muhammad Siddiq (Jurnal Konstitusi, 2016)
After more a decade, Indonesian Constitutional Court (ICC) has importantly played a significant role in the law reform, such  as  protecting  energy  security  through  their judgements. ICC comes out of the box, creating unpredictable judgements, and ensuring the justice values. In protecting energy security ICC makes important breakthrough with reviewing Act Number 22 of 2001 on the Oil and Earth Gas, Act Number 4 of 2009     on the Mineral Mining and Coal, and invaliding Act Number 20 of 2002 on the Electrical Power. Those acts contradict the basic norm in the 1945 Constitution. Although creating public debate, ICC judgment should be   appreciated.